Development of Gas Detector Using Arduino UNO - Anak Kurong, Michael Agah; Ganteh, Mohammad Abdullah; Kumar, Sharvin; Hussin, Ahmad Faiz; Yusof, Khairul Huda; Amirrudin, Nurul ‘Ain; Md. Sapari, Norazliani (Multidisciplinary Applied Research and Innovation, 2024)
This study presents a gas alert system, designed and implemented using an Arduino Uno microcontroller and an MQ135 gas sensor. The system is aimed to monitor indoor air quality by detecting a range of hydrocarbon gases, such as propane, propylene, butylene, isobutane, and butane, commonly found in LPG (Liquefied Petroleum Gas) fuel gas. Its primary purpose is to measure target gas levels, be constantly and accurately prepared for rapid response to dangerous situations, and instantly set off alarms when gas concentrations surpass predetermined safety limits, warning occupants of potential hazards. The sensor MQ135 is used in this project to detect gas level concentration. Arduino UNO functions to monitor air quality levels in designated rooms and process the data, shown on 16X2 LCD display module. The project outputs are a sign light and a bell to sound an alarm. Both gas detectors and the crucial safety factors are highly helpful in identifying gas in buildings. In addition to detecting gas in the air, a gas detector circuit reads and displays its amount. If the gas level rises above the desired level, this circuit will activate the buzzer.